Waiting impulsivity during reward seeking increases adult hippocampal neurogenesis in mice. (27th July 2019) - Peyton, Lee; Oliveros, Alfredo; Cho, Chang Hoon; Starski, Phillip; Lindberg, Daniel; Jang, Mi-Hyeon; Choi, Doo-Sup
Highlights: Impulsive reward seeking increases the number of BrdU labeled cells in the dentate gyrus region of the hippocampus. Impulsive mice exhibit increased colocalized BrdU + and NeuN + neurons compared to control mice. Waiting impulsivity may stimulate adult hippocampal neurogenesis during reward seeking behavior. Abstract: Impulsivity is defined as a predisposition toward rapid, unplanned reactions in response to internal or external stimuli, often yielding negative consequences. Accordingly, impulsivity is considered a significant risk factor for developing addictive behaviors. The hippocampus is involved in regulating behavioral adaptability and learned behaviors. Consequently, abnormal hippocampal function has been demonstrated to contribute to impulsive and addictive behaviors. Furthermore, differential reinforcement of low rates of behavior (DRL) has shown that the hippocampus is implicated in reward acquisition and impulsivity in humans and rodent models. We have previously shown that impulsive behavior potentiates hippocampal neuroblast proliferation. However, the fate of these precursor cells produced during impulsive reward seeking remains unknown. Here, we demonstrate that DRL-mediated impulsive reward seeking with the 2-choice reaction time task (2-CRTT) increases the number of BrdU labeled cells in the dentate gyrus region of the hippocampus. Importantly, our results also show a significant increase in BrdU + and NeuN + colocalized mature newborn neurons in mice exhibiting impulsivity compared to non-impulsive control mice. These results suggest that operant reward seeking during unpredictable schedules of reinforcement contributes to adult hippocampal neurogenesis.